Design of Electronic Voting Machine using Raspberry Pi - M. Anusha, Dr. M. Reji (International Journal of Control and Automation, 2020)
Electronic casting a ballot machine (EVM)has been created and generally utilized in many created countries to further improve the decision procedure and to abstain from gear, yet the greater part of them utilize radio frequency ID. Utilizing RFID is an expensive arrangement. Here we are going to fabricate an electronic voting machine utilizing a raspberry pi board. As we all know that the electronic voting machine is used to cast a ballot in electronics. The distinctive microcontrollers like an electronic voting machine with AVR microcontrollers and EVM with Arduino are utilized by the secured EVM. We have assembled a voting machine in which voter is confirmed by RFID tag, with the goal that just verified votes can be tallied or counted. This electronic voting machine utilizing raspberry pi is not a difficult and not demanding one, in examination with our past voting machine projects. The picture handling system is used by creating nations to distinguish natives. The picture preparation is not enough for security criteria in any case.